Persistence of Carbaryl in Sandy Loam Soil and its Uptake in Bajra, Pennisetum Typhoides P. - Gangar, S K; Kavadia, V S; Gupta, H C L; Srivastava, B P (Annals of Arid Zone, 2016)
Application of carbaryl 4% granules in different dosages in furrows in sandy loam soil results in variable deposits but residues do not persist for more than 90 days under the influence of several factors. The uptake of insecticide in bajra plants grown on treated soils at different growth periods is below detectable level The grains also do not contain residues of insecticide, hence safe for consumption.